Reaching for the Tree of Life: The Role of Eating, Drinking, Fasting, and Symbolic Foodstuffs in 4 Ezra - Smit, Peter-Ben (Journal for the study of Judaism, 2014)
This paper considers the role of foodstuffs and their (non-)consumption in 4 Ezra. While foodstuffs figure prominently in 4 Ezra, no prior research has been conducted on food and 4 Ezra. The paper argues that both the narrative progression of the work and significant parts of 4 Ezra are expressed through foodstuffs.